FORMULASI HANDSANITIZER DENGAN BAHAN AKTIF SIRIH (Piper betle L.), LIDAH BUAYA (ALOE VERA (L.) BURM. F..) DAN MINYAK ATSIRI SEREH WANGI (CYMBOPOGON WINTERIANUS JOWITT) UNTUK MENCEGAH COVID-19 - andila, putri sri (Buletin Udayana Mengabdi; Vol 19 No 3 (2020): Buletin Udayana Mengabdi, 2020)
In order to prevent the spread of Covid 19 and the implementation of health protocols in the "New Normal" era, Eka Karya Botanic Garden produced a hand sanitizer with active ingredients of Piper (P. betle), Aloe vera (A. vera and citronella essential oil (C. winterianus). This hand sanitizer is made with active ingredients consisting of 96% ethanol, Piper leaf extract ( P. betle ), Aloe Vera gel ( A. vera ), and citronella essential oil ( C. winterianus ). All ingredients are mixed with a ratio of 80% ethanol and a mixture of Piper extract, Aloe vera gel, and essential oil as much as 30%. After that to determine the feasibility and acceptance of the respondents to the hand sanitizer produced, an acceptability test was carried out and an allergy test was required. This test was conducted on 83 respondents who were asked to use a hand sanitizer. Base on acceptability testing, it was found that 77 people (92.8%) liked this hand sanitizer product and 6 people (7.23%) did not like it. This result correlated with the allergy test results where as many as 5 respondents (6.02%) experienced allergies from mild to moderate. This product can be recommended as an antiseptic provided that you must pay attention to allergic reactions after use.